Drevo želanija The wishing tree - Kvernadze, Bidzina 1928-2010; Bobokhidze, Jakob 1931-2007 (RUSCICO, 2000)
Second part of Tengiz Abuladze's trilogy (The Plea, The Wishing Tree, Repentance) is based on the stories of Georgi Leonidze about his childhood
Originally produced as a motion picture 1976 by Gruzia-Film
Früheres Copyright: 1977
Based on the short stories of GeorgiiÌ Leonidze
Keywords: Love / Drama; Georgia (Republic) / Social life and customs / Drama; Love; Manners and customs; Georgia (Republic); Foreign language films / Georgian; Foreign language films / Russian; Drama; Feature films; Film; DVD-Video